Perfil epidemiológico, clínico, histopatológico, imunohistoquímico e do tratamento de mulheres diagnosticadas com câncer de mama na zona norte do estado do Ceará - Rangel Filho, Francisco Airton (2024)
Introduction: Breast cancer is the most common neoplasm among women in Brazil and worldwide. In Brazil, statistical studies have shown a reduction in the incidence and mortality of breast cancer in recent years. However, the negative social and economic impact of this disease is still significant. Therefore, investing in new epidemiological and etiopathogenic knowledge on this disease is of significant importance in public health.Objectives: To assess the epidemiological, clinical, histopathological, immunohistochemical, and treatment profile of women diagnosed with breast cancer in the northern region of the state of Ceará.Methodology: Retrospective, quantitative, epidemiological, cross-sectional, analytical, and observational study conducted through the analysis of data collected from the medical records of patients with breast cancer treated at the oncology sector of Santa Casa de Misericórdia de Sobralhospital from 2018 to 2023. We used a research instrument developed by the research group, through a pre-standardized form and statistical analysis using the X2 test, with a value of p≤0.05 being considered significant.Results: Two hundred and forty-two women were included in this study and after reviewing the inclusion and exclusion criteria, 204 medical records were valid for the study. Mean age was 55 years, 36.3% of whom were premenopausal. Most patients were in clinical stage II (42.6%) and the initial diagnosis of locally advanced disease was present in 35.3% of the cases. The most frequent molecular subtype was Luminal B (49.4%). The most frequent histological type was invasive ductal carcinoma (75.2%).Conclusion: The clinical-pathological-molecular profile of breast cancer in patients treated in the northern region of the state of Ceará, Brazil, was well defined in this study. The above data demonstrated that screening for early detection needs to be better implemented in our region and finally, this research gains relevance for being a pioneer in an in-depth analysis of the profile of patients withbreast neoplasm in this region of the country.